2020
DOI: 10.21873/anticanres.14413
|View full text |Cite
|
Sign up to set email alerts
|

Coprevalence and Incidence of Lung Cancer in Patients Screened for Abdominal Aortic Aneurysm

Abstract: Background/Aim: Lung diseases are common in patients with abdominal aortic aneurysms (AAA). This study evaluates the prevalence of lung cancer (LC) in high-risk patients screened for AAA. Patients and Methods: Six hundred and one male patients (≥65 years of age, cardiovascular highrisk profile) were enrolled and followed prospectively over a median of 16.5 months. Results: In 29 patients (4.8%) LC and in another 50 patients (8.3%) AAA were found. The prevalence of LC among patients with AAA was even higher (9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Despite improvements in short-term outcome after AAA repair, late survival has not improved, even after successful repair 17 , 18 . Previous studies have suggested a high prevalence of AAA in patients with lung cancer 6 , 19 . It is not clearly demonstrated whether this is a simple co-occurrence or if there is an association between the two diseases 20 .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Despite improvements in short-term outcome after AAA repair, late survival has not improved, even after successful repair 17 , 18 . Previous studies have suggested a high prevalence of AAA in patients with lung cancer 6 , 19 . It is not clearly demonstrated whether this is a simple co-occurrence or if there is an association between the two diseases 20 .…”
Section: Discussionmentioning
confidence: 92%
“…There has been an increase in reports of concomitant AAA and malignancy, and an estimated 1.0–17.0% of patients with AAA have or develop a concomitant malignancy 4 , 5 . Both AAA and malignancy have a tendency to increase in prevalence with age 6 , 7 . In addition to advanced age, coexistence of these diseases may be attributable to similar patient demographics and common risk factors such as smoking 8 .…”
Section: Introductionmentioning
confidence: 99%
“…One-stage open procedure can be used well for patients with renal carcinoma and patients with tumours of the small and large intestine (in particular on the ascending and transverse colon) and liver (28). For bowel surgery it is recommended that the AAA resection first be performed, and then after coverage of the vascular prosthesis with AAA wall, rear sheet of retroperitoneum (sometimes even omentum) and draping with anti-septic drapes, perform bowel resection with minimisation of possible infection of vascular reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…The suggested mechanisms of coexistence of AAA and malignancies include common risk factors, proinflammatory conditions and oxidative stress. AAA shares a number of modifiable risk factors with cancer, such as smoking and increased age [4,8,32]. It has also been suggested that it might be due to the presence of chronic inflammatory cells and cytokines and the angiogenesis status in patients with AAA [32].…”
Section: Discussionmentioning
confidence: 99%
“…In an aging population, multimorbidity is frequent. Various diseases show an agerelated prevalence, and some morbidities often coincide due to shared risk factors [4]. Cancer is not uncommon in patients with an AAA; as a result, concomitant cancer and AAA has been a long-standing subject of study in deciding the treatment priority and method [5,6].…”
Section: Introductionmentioning
confidence: 99%